The dual-factor model of female volleyball student athlete mental health: A scoping review - Enderle, H.; Ormiston, H. E.; Lim, H. S.; Koch, M.; Spicer-Gordon, R.; Minix, A. L. (Journal of Clinical Sport Psychology, 2026)
There is a dearth of literature examining female volleyball student athlete mental health. In alignment with the major stakeholders in student athlete mental health`s call for care to move toward a model that includes examining athlete well-being alongside psychopathology, we examined the existing research related to this population`s mental health. Employing the Dual-Factor Model of Mental Health which utilizes both subjective well-being and psychopathology in its definition of mental health to provide a more nuanced, holistic, and accurate foundation for identifying individual mental health needs, we conducted a scoping review to identify existing research on female volleyball student athlete mental health. Review results indicated 16 studies met our inclusion criteria while four ( n = 4) study measures examined both constructs within the same study. The study results also indicated a severe lack of research conducted with minoritized populations. Study limitations, directions for future research, and implications for practice are discussed.